Is There an Immigration and School-Level Crime Link?. (July 2023) - Peguero, Anthony A.; Irizarry, Yasmiyn; Iwama, Janice; King, Sanna; Dunning-Lozano, Jessica L.; Hong, Jun Sung; Bondy, Jennifer M.
Contrary to the public misperception that immigrants are likely to be involved in criminal activities, evidence suggests that immigrants are less likely to engage in violence and criminal behavior at the individual level. Little is known, however, about the relationship between immigration, violence, and delinquency at the school-level. The present study draws from the nationally representative 2015 to 2016 School Survey on Crime and Safety to address two research questions. First, is there an association between an increasing proportion of immigrant students and school-level crime? Second, are there racial/ethnic differences in the association between increasing proportion of immigrant students and school-level crime? Our results indicate no relationship between immigration and school-level crime; however, important and distinctive nuances are related to the study findings.